SEX-RELATED DIFFERENCES IN PHYSICAL FITNESS COMPONENTS AMONG YOUNG SCHOOL-AGE CHILDREN: A CROSS-SECTIONAL STUDY - Mijalković, Stefan; Stojanović, Stefan; Ilić, Tamara; Volaš, Dejan; Purenović-Ivanović, Tijana (Physical Education and Sport Through The Centuries, 2026)
The aim of this study was to examine sex-related differences in fitness components among young school-age children. A total of 138 children (72 boys and 66 girls; mean age 9.08 ± 0.67 years) participated in this cross-sectional study. Body composition, motor abilities, and cardiorespiratory parameters were assessed using standardized field-based tests. Differences between boys and girls were analyzed using the independent samples Student’s t-test or Mann–Whitney U tests, depending on data distribution. The results revealed that boys had significantly higher muscle mass percentage, faster sprint times, better agility, greater explosive power of both the lower and upper limbs, higher aerobic capacity, and lower resting heart rate compared to girls (p < 0.05). No significant differences were observed in body height, body mass, body mass index, body fat percentage or blood pressure parameters. These findings indicate that sex-related differences in multiple fitness components are evident already in early school age, providing important insight into the early emergence of distinct physical fitness profiles between boys and girls.